Epilepsy as a Neurodevelopmental Disorder - Bozzi, Yuri; Casarosa, Simona; Caleo, Matteo (Frontiers in Psychiatry, 2012)
Epilepsy is characterized by spontaneous recurrent seizures and comprises a diverse group of syndromes with different aetiologies. Epileptogenesis refers to the process whereby the brain becomes epileptic and can be related to several factors, such as acquired structural brain lesions, inborn brain malformations, alterations in neuronal signalling and defects in maturation and plasticity of neuronal networks. In this review, we will focus on alterations of brain development that lead to an hyperexcitability phenotype in adulthood, providing examples from both animal and human studies. Malformations of cortical development (including focal cortical dysplasia, lissencephaly, heterotopia, and polymicrogyria) are frequently epileptogenic and result from defects in cell proliferation in the germinal zone and/or impaired neuronal migration and differentiation. Delayed or reduced arrival of inhibitory interneurons into the cortical plate is another possible cause of epileptogenesis. GABAergic neurons are generated during early development in the ganglionic eminences, and failure to pursue migration towards the cortex alters the excitatory/inhibitory balance resulting in aberrant network hyperexcitability. More subtle defects in the developmental assembly of excitatory and inhibitory synapses are also involved in epilepsy. For example, mutations in the presynaptic proteins synapsins and SNAP-25 cause derangements of synaptic transmission and plasticity which underlie appearance of an epileptic phenotype. Finally, there is evidence that defects in synapse elimination and remodelling during early “critical periods” can trigger hyperexcitability later in life. Further clarification of the developmental pathways to epilepsy has important implications for disease prevention and therapy.